Analisis Kemahiran Membaca Buku Ajar MI Berstandar American Council on Teaching of Foreign Languages (ACTFL) - Mitrajati, Kenyo; Mustofa, Tulus (BASICA Journal of Arts and Science in Primary Education, 2023)
This study discusses content analysis of MI Arabic textbooks for grade VI using ACTFL competency standards. This analysis will later provide a conclusion that the competency in reading the Arabic language textbook shows the appropriate level of competency standards in ACTFL. For each skill, the ACTFL guidelines identify five main levels of proficiency: Distinguished, Superior, Advanced, Intermediate, and Novice. Then start the Advanced (Advanced), Intermediate (Intermediate), and Beginner (Novice) levels. these are further divided into High, Mid, and Low sublevels, respectively. This research is a research with a qualitative approach with content or content analysis methods. Content analysis is a qualitatively oriented technique, standardized measures applied to certain units are usually used to characterize documents or compare them. The data obtained will be analyzed by the author by looking at the concept map and learning objectives of the textbook. The main purpose of writing this research is to complement existing research related to the analysis of MI Arabic textbooks with the ACTFL standard, especially in analyzing reading skills.